ANALISIS FAKTOR SOSIAL EKONOMI YANG MEMPENGARUHI PENDAPATANPETANI KELAPA SAWITDIKECAMATAN RANTAU SELATAN KABUPATEN LABUHANBATU - Khairul Rizal (UNIVERSITAS LABUHANBATU, 2019)
This study aims tofirst find out the socio-economic factors, the second major income contribution, thirdly knowing the feasibility of farming. The study was conducted at Rantau Selatan District, Labuhanbatu Regency. This study uses methods proportionated stratified random sampling. Data were analyzed by linear regression multiple and R / C analysis. The results of the study show that there are simultaneous factors socioeconomic effect on income at a trust level of 95%. Partially the number of plants, fertilizer costs, pesticide costs, and transportation costs significant effect on income, while depreciation costs, equipment costs, land area, workforce in the family, workforce outside the family, number of dependents in the family, the level of education and the selling price have no significant effect on income. Contribution of oil palm farmers' income to total income farmer family of 78.89%. The R / C value is obtained at 2.50 which means that palm oil farming is feasible financially. Keywords :farming, palm oil, socio-economic factors